Pengaruh Secure Attachment Style Terhadap Interaksi Parasosial Pada Dewasa Awal - Wati, Hafizhah Zahrah Hardinda; Savira, Siti Ina (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
Early adulthood has the developmental crisis of forming interactions and relationships. Technological developments have facilitated interactions with media figures. A media figure is an individual, figure, or character that appears through media. Attachment styles are known to be one of the factors that influence the formation of parasocial interactions. A secure attachment style is one attachment style that indicates that individuals have a positive self-concept. This study aims to determine secure attachment style's effect on early adulthood parasocial interactions. The research method used is quantitative with a simple linear regression analysis technique. This research included 359 participants with an age range of 20 to 30 years. The results obtained a significance value of 0.000 (p<0.05), indicating that secure attachment style significantly influences parasocial interactions in early adulthood.